Proyecto de factibilidad para la creación de una compañía de servicios de asesoramiento para pequeñas y medianas empresas del sector de la construcción en la ciudad de Guayaquil en el 2016 - Cabrera Tejada, Lisett Carolina (2016)
This research focuses on the feasibility project for the creation of a company advisory services for small and medium enterprises in the construction sector in the city of Guayaquil in 2016, because it has been observed that SMEs currently has no equal action against large companies in public procurement competitions because they often do not have sufficient capital or because their level of knowledge of the requirements are void. The construction sector in Guayaquil and Ecuador is one of the strongest economic pillar, because it is one that creates more space for employment and that every day the number of works increase especially in the public area where there greater opportunities……..